Impacto das instituições fiscais na condição financeira dos estados brasileiros - Vieira, Luis Manuel Esteves da Rocha (2019)
The Financial Condition of the Brazilian states has been a source of news over the last few years, especially highlighting the fiscal problems faced by these government entities, characterized by late payment of salaries, retirement incomes, suppliers and public debt services. National studies are recent and still incipient regarding the analysis of the specific characteristics of Brazilian Fiscal Federalism and its impact on the explanation of the states Financial Condition. Thus, it was established the thesis that the Fiscal Institutions related to Budgetary Constraints, Financial Autonomy and Revenue Redistribution in Brazilian State Participation Fund (FPE) positively affect the Financial Condition of the Brazilian states depending on the very short-term, short-term and long-term temporal dimensions. Therefore, data was collected from 2002 to 2018, gathering 459 observations from 26 states and the Federal District. Data analysis was performed using static panel regression with fixed effects and Least Square Dummy Variables, and dynamic panel by GMM-Sys method, robust to endogeneity problems. The results revealed that regarding the Brazilian budgetary constraints, the compliance degree with the debt limit contributes to the improvement of Cash Solvency (very short-term) and Long-Term Solvency, while the compliance degree with the personnel spending limit significantly impacts only Budget Solvency (short-term). Regarding Financial Autonomy, it was also found that states with less dependence on transfers tend to have better Budgetary Solvency (short-term). Regarding the Redistribution of Revenue by the Brazilian State Participation Fund (FPE), was found a positive effect on the short-term Financial Condition in terms of Budgetary Solvency, supplying the vertical and horizontal financial gaps of the states. Even so, it should be noted that the form of this Fiscal Institution, regarding the guiding percentage criteria for redistribution, has not undergone any statistically significant changes since the latest Brazilian Constitution of 1988, being possible to observe that several states with poor Financial Condition, including some in situation of declared fiscal calamity, are having their Cash Solvency impaired by contributing superior amounts to the FPE than those received back through fiscal transfers.